Gender and entrepreneurship in Portugal - Nunes, Alcina (2018)
Entrepreneurship is an international phenomenon which creates, innovates and generates employment, and, therefore, economic growth. In individual terms, it arises as a new perspective of career for both men and women. In Portugal, research on this topic is relatively scarce. Thus, the purpose of this research work is to quantify the entrepreneurial phenomenon by gender in Portugal in the first decade of the XXI century. In order to achieve this goal has been applied logistic regression models to the Global Entrepreneurship Monitor (GEM) secondary data. It was found that entrepreneurial activity differs in gender in Portugal. In the Portuguese economy, men start ventures more frequently than women, and, taking into account the last year analysed, men are twice more likely to start a new business than women. This figure had previously been three times superior, which shows that women are demonstrating an increasing interest in entrepreneurship.